2019
DOI: 10.3390/en12101927
|View full text |Cite
|
Sign up to set email alerts
|

Energy Recovery from Sewage Sludge: The Case Study of Croatia

Abstract: Croatia produced 21,366 tonnes of dry matter (DM) sewage sludge (SS) in 2016, a quantity expected to surpass 100,000 tonnes DM by 2024. Annual production rates for future wastewater treatment plants (WWTP) in Croatia are estimated at 5.8–7.3 Nm3/people equivalent (PE) for biogas and 20–25 kgDM/PE of sewage sludge. Biogas can be converted into 12–16 kWhel/PE of electricity and 19–24 kWhth/PE of heat, which is sufficient for 30–40% of electrical and 80–100% of thermal autonomy. The WWTP autonomy can be increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 31 publications
(37 reference statements)
0
51
0
1
Order By: Relevance
“…Twenty-seven European Union countries generated more than 11.5 million tons of sewage sludge in 2015, and this quantity is expected to increase up to 13 million tons by 2020 due to industrialization and urbanization [2][3][4][5]. In the past few years, European Union promoted the ecological management of such wastes by introducing directives regarding sewage sludge management and therefore classical methods, such as storage, are being replaced by methods leading to waste stabilization and safe recycling.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-seven European Union countries generated more than 11.5 million tons of sewage sludge in 2015, and this quantity is expected to increase up to 13 million tons by 2020 due to industrialization and urbanization [2][3][4][5]. In the past few years, European Union promoted the ecological management of such wastes by introducing directives regarding sewage sludge management and therefore classical methods, such as storage, are being replaced by methods leading to waste stabilization and safe recycling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the efficiency of sludge bioconversion is low because of flocculation that hinders microbial degradation 7 . Current disposal techniques such as incineration, landfill, and agricultural usage have been discouraged, as they impact public health and the environment 8,9 . Instead, anaerobic digestion has become increasingly important as an economic and sustainable solution for sludge reduction and stabilization because of its efficient organic matter reduction and the possibility of energy recovery from the generated biogas 10 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Current disposal techniques such as incineration, landfill, and agricultural usage have been discouraged, as they impact public health and the environment. 8,9 Instead, anaerobic digestion has become increasingly important as an economic and sustainable solution for sludge reduction and stabilization because of its efficient organic matter reduction and the possibility of energy recovery from the generated biogas. 10 However, the low organic loading rate often leads to inferior treatment performance of sludge digesters.…”
mentioning
confidence: 99%
“…However, in recent years sewage sludge has gained attention as a promising source for biofuel production [3]. Many studies have suggested anaerobic digestion or fermentation and the direct use (through incineration after drying) of sewage sludge [4], but the low biological conversion efficiency and high energy consumption during sewage sludge drying are drawbacks of these methods. Recently, the high lipid content of sewage sludge has been gaining worldwide attention as a possible feedstock, owing to its low cost and availability, as it is an abundant organic waste [5].…”
Section: Introductionmentioning
confidence: 99%